Study on Optimization of Law Number 23 of 2011 concerning Management of Zakat in Bengkulu City in Giving Productive Zakat (JURNAL HUKUM SEHASEN, 2020)
Effectiveness in increasing the amount of zakat, infaq and alms, BAZNAS's efforts in collecting are socialization to the community, so that people are aware of paying their ZIS. Then to be more effective, BAZNAS coordinates with UPZs in Bengkulu to help disseminate information to colleagues and the surrounding community to raise their awareness of paying ZIS to develop the economy of people who need it, especially people who want to try to improve the economy. This research uses field research (field research) using qualitative descriptive methods. Descriptive research to analyze the data that the authors have obtained, the authors use a comparative analysis method, namely research that aims to compare systematically, factually, and accurately about facts, situations or events that exist in the field.